Prevalence of overcoming and obesity in pre-schools in Brazil: an integrating review (Research, Society and Development, 2020)
This article presents results of an integrative literature review on the prevalence of overweight and obesity in preschoolers in Brazil, which sought to analyze prevalence in different regions of the country considering types of study, indicators of nutritional status, associated factors, among other aspects. Virtual Health Library (BVS-BIREME), Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed) e Scientific Eletronic Library Online (SciELO), databases were used, using a combination of Boolean terms and operators: Obesity (OR) overweight (AND) prevalence (AND) child, preschool (AND) brazil. All articles published up to the time of the research, in English, Spanish and Portuguese, were included in the search. The search took place in June 2019. Using the combination of Boolean descriptors and operators, 585 articles were found. Of these, 327 were excluded by repetition, by reading 258 excluded titles and abstracts, totaling 30 articles for analysis. Most of the studies were carried out between 2008 and 2012, with the most frequent regions of the country, Northeast and Southeast. Most of the studies were cross-sectional, with great diversity in the sample size. For the diagnosis of nutritional status, different types of indicators were used, with some studies using only one type and other multiple indicators. As for the associated factors, they also showed variability. Studies show a tendency towards an increase in the prevalence of overweight and obesity in the last two decades, indicating clearly epidemic behavior of the problem.